2021
DOI: 10.1038/s41598-021-91698-y
|View full text |Cite
|
Sign up to set email alerts
|

Cystine–glutamate antiporter deletion accelerates motor recovery and improves histological outcomes following spinal cord injury in mice

Abstract: AbstractxCT is the specific subunit of System xc-, an antiporter importing cystine while releasing glutamate. Although xCT expression has been found in the spinal cord, its expression and role after spinal cord injury (SCI) remain unknown. The aim of this study was to characterize the role of xCT on functional and histological outcomes following SCI induced in wild-type (xCT+/+) and in xCT-deficient mice (xCT−/−). In the normal mouse spinal cord, slc7a11/xCT mRNA was detected in meningeal fibroblasts, vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Finally, blockade of glutamate receptors eliminated the differences in AD latency between xCT −/− and WT mice, suggesting that the lower levels of tonic glutamate in xCT −/− mice delay AD by slowing the activation of postsynaptic glutamate receptors during anoxia. These results reinforce, extend, and interpret findings of reduced neuronal death after ischaemic challenge in cell culture systems (Hsieh et al, 2017;Jackman et al, 2012;Soria et al, 2014;Thorn et al, 2015) as well as protection from epileptogenesis (De Bundel et al, 2011;Leclercq et al, 2019;Sears et al, 2019), cerebral ischaemia (Hsieh et al, 2017) and spinal cord injury (Sprimont et al, 2021) in vivo when system x c − is absent or inhibited.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, blockade of glutamate receptors eliminated the differences in AD latency between xCT −/− and WT mice, suggesting that the lower levels of tonic glutamate in xCT −/− mice delay AD by slowing the activation of postsynaptic glutamate receptors during anoxia. These results reinforce, extend, and interpret findings of reduced neuronal death after ischaemic challenge in cell culture systems (Hsieh et al, 2017;Jackman et al, 2012;Soria et al, 2014;Thorn et al, 2015) as well as protection from epileptogenesis (De Bundel et al, 2011;Leclercq et al, 2019;Sears et al, 2019), cerebral ischaemia (Hsieh et al, 2017) and spinal cord injury (Sprimont et al, 2021) in vivo when system x c − is absent or inhibited.…”
Section: Discussionsupporting
confidence: 83%
“…Emerging evidence suggests that specific subtypes of immune cells can reduce pain and contribute to the resolution of NP [ 48 , 63 ]. Previous studies have evidenced that activated microglia show increased system x c − expression and that the genetic invalidation of xCT alters their polarization profile, predominantly adopting a protective anti-inflammatory (M2) phenotype in the spinal cord of animal models of neurological diseases such as amyotrophic lateral sclerosis [ 19 ] or spinal cord injury [ 64 ]. In line with this observation, our findings indicate that mice lacking xCT exhibit a different polarization profile of microglia as compared to their wild-type counterparts, suggesting that the absence of system x c − could beneficially balance the strong pro-inflammatory activation state commonly observed in the context of NP.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have revealed the significantly upregulated expression of SLC7A11 in tumor-associated macrophages (TAM). And knocking out SLC7A11 in these macrophages significantly diminished the infiltration of TAMs and hindered the shift to an M2-like phenotype in HCC tissues, which in turn attenuated tumor growth and metastasis [37]. Prior investigations have concentrated on the role of ferroptosis in tumor cells, highlighting how SLC7A11mediated ferroptosis and phenotypic alterations in TAMs profoundly modify the HCC tumor microenvironment and promote tumor proliferation [38].…”
Section: Discussionmentioning
confidence: 99%